‘Marxcelerationismen’ – Et historiefilosofisk kerneproblem i marxismens historie - Routhier, Dominique (Slagmark - Tidsskrift for idéhistorie, 2018)
'MARXCELERATIONISM' - A HISTORICO-PHILOSOPHICAL IN THE HISTORY OF MARXISM This article reconstructs anew the correspondence that took place in 1881 between Marx and the Russian revolutionary Vera Zasulich. In this correspondence, initially about the Russian ‘agrarian question’, a much broader historico-philosophical issue was fundamentally at stake: the idea of progress. In the ill-fated history of Marxism the idea of progress has, arguably, served to bolster a politics of modernization partly shielded from criticism by the very fact that it allegedly originated in Marx’s so called theory of history. This article argues, on the contrary, that Marx held no such universal theory of history at all. Instead, Zasulich’s and subsequently Lenin’s appeal to an ‘acceleration’ of the contradictions of capitalism to promote the presumably inevitable historical passage to socialism (a view that this article in a contemporary pun identifies as ‘marxcelerationist’) is construed as part and parcel of a Marxist ideology of progress unequivocally criticized by Marx himself as early as in 1881.